A Study on Harmonious Coloring of Circulant Networks - Thamil Selvi.M.S, Franklin; A, Amutha; A, Antony Mary (International Journal of Engineering and Technology, 2018)
Given a simple graph , a harmonious coloring of  is the proper vertex coloring such that each pair of colors seems to appears together on at most one edge. The harmonious chromatic number of , denoted by  is the minimal number of colors in a harmonious coloring of . In this paper we have determined the harmonious chromatic number of some classes of Circulant Networks.